INFLUENCE OF TRANSPORTATION DISTANCE ON THE COST OF RENTAL GROUP VEHICLES IN THE CITY - K. P. Krylova; E. E. Vitvitskiy (Вестник СибАДИ, 2017)
The article considers the theory and practice of rental group vehicles in the transportation of commercial cargo on the pendulum route with reverse not loaded mileage in the cities. Transportation is carried out by vehicles of the same capacity and same brand, a method of accomplishment of handling works– manually. Dependence of the cost of rental group vehicles from the change of transportation distance is established. Check installed dependencies on the adequacy to process of costs forming is executed.